Active Learning - Muhammad Hufron (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2020)
The purpose of this study was to analyze the effect of the Jigsaw method (X1) and the Quiz Team (X2) method on the Courage of Opinion (Y). In this study, data were collected through questionnaire techniques on students of Islamic Education Department respondents in the Faculty of Education and Teaching Sciences on IAIN Pekalongan by using cluster sampling method to determine respondents' responses to each variable. The data is processed so as to produce multiple regression equations as follows: Y = (28,228) + (-0,148) X1 + (0,596) X2. The results of the analysis found that the Jigsaw method and the Quiz Team method simultaneously had a positive and significant influence on Courage of Opinion. Hypothesis testing using t test shows that the Jigsaw method has proven to be insignificant towards Courage of Opinion of -0.148. Whereas the Quiz Team method is proven to be significant and influences the Courage of Opinion of 0.596. Then through the F Test can be known the Jigsaw method and the Quiz Team method both simultaneously influence positively and significantly in increasing Courage of Opinion.